Neologizmy artystyczne jako przedmiot badań nad poprawnością językową (na materiale wybranych utworów Jacka Dukaja) - Mikołajczak, Ilona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The purpose of this study was to present the conclusions about checking artistic neologisms for lingustic corectness. The article begins the review of contemporary source literature that gradually eliminate fiction from resarch on linguistic corectness, in spite of long-standing tradition of using literary works. Then the author passes on a detailed analysis of criteria of linguistic corectness developed by Warsaw School of Lingustics, chosing Jacek Dukaj’s prose as subject of resarch and defending this choice. Futhermore, excerpts the fulfiling the criteria examples or not, also raises the questions of usefulness of all the criteria and the reference to category of literary genre, and what can be the mistake in fiction. The effect of this investigation is new hierarchical compilation of linguistic corectness criteria, created for the purposes of the codification.